Maia variables and other anomalies among pulsating stars - Balona, L. A. (Frontiers in Astronomy and Space Sciences, 2023)
High-precision photometry from TESS has revealed over 500 stars, located between the δ Scuti and β Cephei instability strips, which pulsate with high frequencies. Models do not predict high pulsation frequencies in these stars. These anomalous variables may be identified with the historical “Maia” variables. From the projected rotational velocities, it is shown that the rotation rates of Maia variables are no different from main sequence or SPB stars in the same effective temperature range. Some Maia stars pulsate at frequencies typical of roAp stars. It is shown that Maia stars should be considered an extension of δ Scuti variables to effective temperatures as high as 18,000 K, rather than as a separate class. The TESS data show a continuous sequence of low-frequency pulsating stars linking the γ Doradus and SPB variables, which is not predicted by the models. There are, in fact, no well-defined instability strips at all among upper main sequence stars, which means that arbitrary choices of effective temperature and frequency ranges need to be made in order to assign a particular variability class. It seems that a mixture of driving mechanisms is present in which convection may play a very important role.